2018
DOI: 10.1186/s12864-018-5107-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification, characterization and expression analysis of the VQ motif-containing gene family in tea plant (Camellia sinensis)

Abstract: BackgroundVQ motif-containing (VQ) proteins are plant-specific proteins that interact with WRKY transcription factors and play important roles in plant growth, development and stress response. To date, VQ gene families have been identified and characterized in many plant species, including Arabidopsis, rice and grapevine. However, the VQ gene family in tea plant has not been reported, and the biological functions of this family remain unknown.ResultsIn total, 25 CsVQ genes were identified based on the genome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 41 publications
(88 reference statements)
2
41
0
2
Order By: Relevance
“…On the contrary, four genes (NtVQ11, NtVQ12, NtVQ20, and NtVQ23) encode protein of more than or equal to 400 amino acids. Furthermore, in silico prediction of the subcellular localization of the encoded NtVQ proteins showed that the majority localize to the nucleus ( Supplementary Table S3), which is similar to many known plants, such as Arabidopsis [11] and tea [23]. Thus, this VQ family appears to be a relatively conserved family evolutionarily.…”
Section: In-silico Analysis Of Ntvq Genesmentioning
confidence: 72%
See 2 more Smart Citations
“…On the contrary, four genes (NtVQ11, NtVQ12, NtVQ20, and NtVQ23) encode protein of more than or equal to 400 amino acids. Furthermore, in silico prediction of the subcellular localization of the encoded NtVQ proteins showed that the majority localize to the nucleus ( Supplementary Table S3), which is similar to many known plants, such as Arabidopsis [11] and tea [23]. Thus, this VQ family appears to be a relatively conserved family evolutionarily.…”
Section: In-silico Analysis Of Ntvq Genesmentioning
confidence: 72%
“…Analysis of the phylogenic tree of tobacco VQ proteins has shown that the clades are similar to those described for Arabidopsis [11] and tomato [24]. Tobacco NtVQ protein has an average of 223.5 amino acids, which is similar to the known VQ protein in many plants, where most of the VQ genes encode fewer than 300 amino acids, including Arabidopsis [11], rice [12], maize [16], Moso bamboo [18], apple [20], poplar [15], Chinese Cabbage [14], soybean [22], tomato [24], tea [23], and so on. On the contrary, four genes (NtVQ11, NtVQ12, NtVQ20, and NtVQ23) encode protein of more than or equal to 400 amino acids.…”
Section: In-silico Analysis Of Ntvq Genesmentioning
confidence: 73%
See 1 more Smart Citation
“…This can be explained by the fact that some promoter sequences may encompass multiple TFBSs of perhaps interacting TFs. Indeed, TFs have been reported to frequently operate in combination (Guo et al, 2018; Kumar et al, 2018). Combinatorial regulation is required to confer specific responses in a particular tissue and under a particular stress.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous report, we performed an Illumina RNA sequencing (RNA-Seq) to compare the transcriptomes of tea plants treated with and without NaCl, and many differentially expressed mRNAs involved in signal transduction pathways, transcription factors (TFs), and other functional genes under salt stress were identified (Wan et al, 2018). Previous reports have also shown that many mRNAs and proteins in tea plants, such as CsSnRK2 (Zhang et al, 2018), CsAQP (Yue et al, 2014), and CsVQ (Guo et al, 2018), respond to salt stress. Long non-coding RNAs (lncRNAs) are important regulatory factors that respond to various abiotic stresses in plants; however, their functions in responding to salt stress have not been studied in tea plants.…”
Section: Introductionmentioning
confidence: 99%